Financial and fiscal policies : crises and new realities - Venugopal Reddy, Y.; Valluri, Narayan; Ray, Partha (New Delhi : Oxford University Press, 2014)
In the backdrop of the experience of the on-going crisis in the global economy, this book seeks to address the emerging challenges to monetary, financial and fiscal policies. To this end, policy challenges are analyzed based on select country experiences (especially, euro-area economies and India) and evolution of their fiscal positions. Emerging issues, such as, public debt management debt restructuring, taxation and regulation of financial sector, are detailed.
Includes bibliographical references (pages 319-333) and index.
aia 05/12/2017
Loans
Keywords: Fiscal policy; Financial crises; Global Financial Crisis, 2008-2009.; Expenditures, Public; Finance, Public; India; Europe--European Union countries; Eurozone